Laboratory Evaluation of Railway Ballast Consolidation by the Non-Destructive Testing - Mykola Sysyn; Vitalii Kovalchuk; Ulf Gerber; Olga Nabochenko; Bogdan Parneta (Communications - Scientific letters of the University of Zilina, 2019)
The property of railway track to resist the irreversible deformation for a long-term operational loading considerably depends on the ballast layer. The ballast layer is the element of a railway track whose mechanical properties and state are formed in-situ with the help of the ballast cleaning, tamping and distributing machines. The varied properties of the ballast material to obtain the form during the maintenance and retain it during the operation are equally important for the ballast layer. The control over the processes of the ballast consolidation and deconsolidation by means of measurement methods could potentially provide great possibilities for improvement of its properties both during the maintenance and operation. The paper deals with an experimental study of the railway ballast consolidation and deconsolidation processes under the vibration loading of the sleeper. A non-destructive measurement method is proposed to investigate the distribution of the ballast consolidation along the sleeper. The method is based on the measurement of time of mechanical wave propagation. Modern low-cost sensors and powerful microcontroller techniques enable creating smart measurement systems for automatic multi-point data acquisition, online processing and statistical estimation of the ballast consolidation distribution.